Personal finance - Kapoor, Jack R. 1937-; Dlabay, Les R.; Hughes, Robert James 1946- (McGraw-Hill/Irwin series in finance, insurance, and real estate, 2015)
Provides practical guidance on how students can achieve peace of mind with regard to their financial situation. This title features many financial planning tools to help students identify and evaluate choices as well as understand the consequences of decisions in terms of opportunity costs.